Etnobotani Tumbuhan Berkhasiat Obat pada Masyarakat Karang Bayan Kabupaten Lombok Barat - Ervina Titi Jayanti (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2022)
Each region has a unique medical culture. The traditional culture of the Sasaknese on Lombok Island has been accustomed to using various types of plants in their traditional medical culture. Those who known to have knowledge and abilities about traditional medicine known as Belian. Knowledge about the types of medicinal plants and the methods and techniques of treatment are generally passed down in the kinship hierarchy.One group of people who are still attached to the tradition of traditional medicine is the special Sasak tribe of the Karang Bayan community, West Lombok. The elders believe that the origin of these communities is from the Bayan region, North Lombok, which is known as a wetu telu area with unique cultural characteristics and relatively preserved local cultural knowledge. Observations, interviews and collection of medicinal plant specimens were carried out in Karang Bayan. Determination of the samples using the snowball method. Data were analyzed descriptively qualitatively by summarizing the results of interviews and parsing various medicinal plants and diseases that are believed to be cured. Furthermore, the data generated and then triangulated (comparing the data obtained with books or journals relating to the research). A total of 47 types of medicinal plants are used to treat 33 types of diseases and symptoms of certain diseases by the Karang Bayan community. Plant parts such as roots, stems, bark, leaves, fruit, seeds, sap, and even the whole plant body are used in medicine. During the compounding process until the application of drugs using certain, Belian (healers) believe that if the procedure is ignored then the patient will not get a cure. This resulted in the formation of strong suggestions in maintaining the traditional treatment procedures for both traditional healers and the patient.